2015
DOI: 10.1017/s1368980015003183
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of nutrition label use among college students and young adults: a review

Abstract: Objective: Nutrition labels are an essential source for consumers to obtain nutrition-related information on food products and serve as a population-level intervention with unparalleled reach. The present study systematically reviewed existing evidence on the correlates of nutrition label use among college students and young adults. Design: Keyword and reference searches were conducted in PubMed, EBSCO, PsycInfo, Cochrane Library and Web of Science. Inclusion criteria included: study design (randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 58 publications
6
45
0
9
Order By: Relevance
“…4,8,11,[16][17][18]21,28 This difference was not apparent for label awareness. This is not the first study to encounter such a result: Hammond and colleagues 29 and Chen and colleagues 27 also found no significant differences in label awareness by sex in college students and adults, respectively.…”
Section: Label Usage -Percent Of Dinersmentioning
confidence: 92%
See 1 more Smart Citation
“…4,8,11,[16][17][18]21,28 This difference was not apparent for label awareness. This is not the first study to encounter such a result: Hammond and colleagues 29 and Chen and colleagues 27 also found no significant differences in label awareness by sex in college students and adults, respectively.…”
Section: Label Usage -Percent Of Dinersmentioning
confidence: 92%
“…3 Nutrition labeling at the point of purchase (or point of selection/service) is a common tool to promote healthier food choices on college campuses (and in the general population) and has been implemented in many dining halls, restaurants, and on-campus convenience stores. Christoph and colleagues 4 reviewed several studies that surveyed US college students' use of food labels; however, findings were highly variable, with reported label use ranging from 35% to 88%, depending on the definition of label use and type of nutrition label considered. For example, some studies focused exclusively on using the Nutrition Facts Panel, whereas others examined general label use or calorie label use in restaurants.…”
mentioning
confidence: 99%
“…78 Additionally, a systematic review of 16 studies found that increased nutrition knowledge and education was associated with nutrition label use in college students. 79 Front-of-package labels, including warning labels of the health harms of consumption of added sugars, could serve to further empower families to make healthier choices. For example, a randomized trial of 2000 adolescents revealed that those who were exposed to a health warning label chose fewer sugary drinks and believed that sugary drinks were less likely to help them lead a healthy life.…”
Section: Children Adolescents and Their Families Should Have Ready mentioning
confidence: 99%
“…Past evidence showed that on-site nutrition policies (e.g., information campaigns) can improve dietary intake, resulting in favorable effects on weight-related outcomes [7]. However, awareness and use of nutrition labels among US university students are still not well understood and are highly dependent on the type of message considered [25].…”
Section: Introductionmentioning
confidence: 99%